COVID-19 PANDEMIC AND DYNAMICS OF HOTEL OWN DEMAND AND SUPPLY IN BALI - Manek, Daniel (CV ODIS, 2021)
The pandemic has paralyzed global tourism. In Bali, the impact of the pandemic on the tourism industry is enormous. Almost all hotels have stopped operating, even if there is an open one, it is also the one that opens itself to quarantine people with COVID. This article examines the condition of hotels in Bali, the demand and supply of rooms to survive during the covid-19 pandemic. This study uses a descriptive qualitative approach by using interviews and literature studies on books, scientific journals, and online news. This research focuses on The Apurva Kempinski for reasons of star level representation and customer type. The results showed that the impact of the pandemic resulted in almost empty hotel occupancy. The strategy is almost the same, namely by laying off employees permanently and temporarily, limiting the use of hotel facilities, spending efficiency, and refusing to refund bookings by changing the visit schedule.